Terror Crime Prevention with Communities - Spalek, Basia (Bloomsbury Academic, 2013)
This book is available as open access through the Bloomsbury Open Access programme and is available on www.bloomsburycollections.com. Historically, countering terrorism has been something that security services have carried out on behalf of the state, without community consultation or consent. Since 9/11 however, this tradition has increasingly been questioned and the idea that communities have the potential to defeat al Qaeda - related or influenced terrorism has gained ascendency across policy, security and other contexts. Based on research in the US, Britain and Northern Ireland, this book examines the involvement of Muslim and other communities in terror crime prevention work, exploring the complexities of community involvement as well as its advantages and examining how trusting relationships between police, security services and communities can be built.